Designing rectangular slot loop antenna for WLAN application - Anantrasirichai, N.; Chanoodhorm, S.; Nakasuwan, J.; Rakluea, P.; Wakabayashi, T. (My University, 2005)
This paper presents the design of rectangular microstrip slot loop antenna that competently achieves dual frequency operation by using a microstrip feed line. This antenna is designed at the resonance frequency 2.4 GHz and 5.2 GHz thereby covering the required frequency-bandwidth of 2.4-2.4836 GHz and 5.15-5.35 GHz, which are widely used in Wireless LAN (WLAN). The characteristics of antennas are proposed and analyzed for instance input impedance, Sn parameter and far field radiation patterns. The antenna is analyzed by Finite Difference Time Domain (FDTD) method which can predict and analysis of the electromagnetic responses of complex problems.
Keywords: FDTD; Rectangular slot; Slot loop antenna; WLAN